THE INFLUENCE OF THYROID FUNCTION AND BONE TURNOVER ON LIPOPROTEIN PROFILE IN YOUNG PHYSICALLY ACTIVE MEN WITH DIFFERENT INSULIN SENSITIVITY - A. Kęska; G. Lutosławska; A. Czajkowska; J. Tkaczyk; K. Mazurek; P. Tomaszewski (Termedia Publishing House, 2014)
Physical activity induces changes in the endocrine system. Previous data indicated that changes in insulin secretion and the tissue response to this hormone are very important for energy metabolism. It is believed that they are accompanied by changes in lipid metabolism, but factors contributing to this process are still disputed. The aim of this study was to assess interactions among insulin sensitivity, thyroid function, a bone turnover marker and serum lipid profile in young physically active men. Eighty-seven physical education students, aged 18-23 years, participated in the study. We measured serum levels of glucose, lipids, insulin, thyroid-stimulating hormone (TSH), osteocalcin and anthropometric parameters. Insulin sensitivity was determined using homeostatic model assessment for insulin resistance (HOMA-IR). The median value of HOMA-IR (1.344) was used to divide the study population into Group A (above the median) and Group B (below the median). Men from both groups did not differ in anthropometric parameters or in daily physical activity. Triglycerides (TG), total cholesterol (TC) and high-density lipoprotein cholesterol (HDL-C) levels were higher in Group A (P<0.05). TSH and osteocalcin levels were similar in males with different HOMA-IR. Multiple regression analysis for TSH and osteocalcin showed that in Group A these hormones had no effect on plasma lipoproteins. However, in Group B they significantly determined the variation of plasma TC and low-density lipoprotein cholesterol (LDL-C) levels (in about 28% and 29%, respectively). We concluded that TSH and osteocalcin are involved in determination of a more healthy lipid profile at a certain level of insulin sensitivity.